White New Zealand rabbits performance fed phosphorus sources containing high fluoride content Desempenho de coelhos Nova Zelândia variedade branca submetidos a fontes de fósforo com altas concentrações de flúor - Walter Motta Ferreira; Artur Canella Avelar (Revista Brasileira de Saúde e Produção Animal, 2009)
Deleterious effects of fluoride content from eight different phosphates were investigated using 30 days white New Zealand young rabbits Oryctolagus cuniculus. Eight differents diet were formulated, each one using a different P source: calcinated bone meal, dicalcium phosphate, super triple phosphate, super simple phosphate, monoammonium phosphate, sulphur amonium phoshphate, ammoniated calcium polyphosphate and a bovine mineral supplement. The zootecnic parameters were followed during 42 days long. At the end of experiment, all animals were slaughtered and livers were collected and weighted. Animals receiving fluoride high level contents (phosphate of amonium and surphur, and bovine mineral salt) have shown the worst results of weight gain feed intake and feed conversion. Os efeitos deletérios do flúor presente em oito diferentes fosfatos foram investigados, utilizando coelhos Oryctolagus cuniculus Nova Zelândia variedade branca na faixa de idade entre 30 até 72 dias. Oito dietas foram formuladas, de acordo com as fontes de fósforo: farinha de ossos calcinada, fosfato bicálcico, fosfato super triplo, fosfato super simples, fosfato mono-amônico, fosfosulfato de amônio, polifosfato de cálcio e amônio e um sal mineral bovino. As variáveis zootécnicas foram acompanhadas ao longo de 42 dias. Os animais foram abatidos e os fígados coletados e pesados. Os animais que receberam dietas formuladas com fosfatos de alto teor de flúor (fosfosulfato de amônio e sal mineral bovino) apresentaram os piores resultados de ganho de peso, de consumo e de conversão alimentar.